Risk Factors Linked to the Occurrence of Neurological Signs Following Poisoning by Cosmetic Products in Morocco (1981-2011) - Bellaje, Rajaa; Sefiani, Houda; Ben Ali, Doha; Adnani, Soufiane; Soulaymani, Abdelmajid; Soulaymani-Bencheikh, Rachida (European Scientific Journal, ESJ, 2026)
Objectives: The objective of this study is to determine the risk factors associated with the onset of neurological disorders during poisoning by cosmetic products. Methods: This is a retrospective study of all cases of poisoning by industrial cosmetic products reported to the Poison and Pharmacovigilance Center of Morocco over a period of 30 years, from January 1981 to the end of December 2011. Results: During the study period, 431 cases were reported with a sex ratio (F/M=1.66). Hair products and skin products are the most incriminated, with 48% and 32.5%, respectively. Clinical signs are described in 51% of cases with a clear predominance of gastrointestinal system disorders (39% of cases), followed by nervous system signs (17.8% of cases). Oral administration was the most common route with 84% of cases. Logistic regression analysis allows us to qualify poisoning by skin lightening creams as the only predictive factor strongly associated with the occurrence of neurological signs (p = 0.011). Conclusions: The establishment of very precise regulations with clarity concerning the law governing cosmetic products will certainly ensure better orientation of care in the event of a declaration of poisoning.